Mapuche educational knowledges: an analysis from the perspective of the Kimches (Polis (Santiago), 2018)
This article presents the kimeltuwün Mapuche educational action to contribute to the solution of the problem involving the contextualization of school contents to teach Mapuche children who begin their schooling process. It is about vernacular knowledge mainly focused on attitudinal contents related to the Mapuche social memory. Educational methods and concepts used by kimches (wise men bearing social and cultural knowledge) to educate children and young people in the family and community context are revealed. To do this, the wise men look upon the sociocultural logic on which their educational knowledge is based. The results show the validity of Mapuche educational knowledge categories in teaching people.
Keywords: educational knowledge; kimün Mapuche knowledge; wise man or kimche